Classification of Newborn Encephalopathy - J Gordon Millichap (Pediatric Neurology Briefs, 1992)
Investigators from the Department of Neurology, Children’s Hospital and Harvard Medical School, Boston and the Neuroepidemiology Branch, Bethesda take issue with the terms hypoxic-ischemic and post-asphyxial encephalopathy when the etiology is frequently in doubt.